Preface - EICCS Editorial Team (Evolution of Information, Communication and Computing System, 2025)
This AI and IoT Integration: Empowering a Connected and Sustainable Future book explores the profound intersection of artificial intelligence, Internet of Things (IoT), and data-driven applications in addressing real-world challenges. Each chapter delves into specialized systems and models developed to solve pressing issues, from environmental monitoring to enhancing public services. This collection seeks to advance understanding and application of AI and IoT in crucial domains, offering a comprehensive resource for practitioners, researchers, and students eager to explore these dynamic technologies. We extend our deepest gratitude to the contributors, whose efforts and insights have enriched this volume. We hope readers find inspiration and valuable knowledge in these pages, empowering them to push the boundaries of innovation.